2012
DOI: 10.1371/journal.pone.0042845
|View full text |Cite
|
Sign up to set email alerts
|

MRI Detects Brain Reorganization after Human Umbilical Tissue-Derived Cells (hUTC) Treatment of Stroke in Rat

Abstract: Human umbilical tissue-derived cells (hUTC) represent an attractive cell source and a potential technology for neurorestoration and improvement of functional outcomes following stroke. Male Wistar rats were subjected to a transient middle cerebral artery occlusion (tMCAo) and were intravenously administered hUTC (N = 11) or vehicle (N = 10) 48 hrs after stroke. White matter and vascular reorganization was monitored over a 12-week period using MRI and histopathology. MRI results were correlated with neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 57 publications
(83 reference statements)
3
41
0
Order By: Relevance
“…In addition to the functional recovery that was observed after hUTC transplantations, previous studies in animal disease models revealed a strong effect of these cells on the preservation of the neural structures (Lund et al, 2007;Jiang et al, 2012;Moore et al, 2013). Therefore, using the RGC culture system, we next examined the effects of UCM on neuronal survival and neurite outgrowth.…”
Section: Ucm Contain Factors That Promote Rgc Survival and Neurite Oumentioning
confidence: 97%
See 4 more Smart Citations
“…In addition to the functional recovery that was observed after hUTC transplantations, previous studies in animal disease models revealed a strong effect of these cells on the preservation of the neural structures (Lund et al, 2007;Jiang et al, 2012;Moore et al, 2013). Therefore, using the RGC culture system, we next examined the effects of UCM on neuronal survival and neurite outgrowth.…”
Section: Ucm Contain Factors That Promote Rgc Survival and Neurite Oumentioning
confidence: 97%
“…The umbilical cord is a commonly used cell source for therapeutic purposes due to ease of accessibility without ethical concerns. Several studies report that umbilical cord blood-derived cells can be potentially useful for the treatment of various types of neuro-degeneration Park et al, 2012;Rowe et al, 2012;Achyut et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations